Biological control of turfgrass diseases with organic composts enriched with Trichoderma atroviride - Coelho, Luísa (2022)
The increasing demand of natural products for the control of plant diseases has led to the search for biological control agents, namely fungi, often isolated from composts of organic residues. By composting two different mixes of agro-industrial residues, P1 and P2 composts were obtained, from where a known antagonist, Trichoderma atroviride, was isolated. Later, a second composting process was performed and when the composting mix reached room temperature, the previously isolated T. atroviride was inoculated in both composts to enrich its population (E) and named as P1E and P2E. The suppressive capacity of these two composts against Sclerotium rolfsii, Clarireedia spp. and Rhizoctonia solani was tested two weeks after T. atroviride inoculation, in 100 mL pots with turfgrass seeded with Agrostis stolonifera. The tested treatments were: composts P1 and P2 without any treatment; thermally treated P1 and P2 (P1t, P2t); P1 and P2 enriched without and with previous thermic treatment (P1E, P2E, P1tE, P2tE), and a commercial peat-based substrate, natural (P) and thermally treated (Pt), enriched (PE) and enriched after thermal treatment (PtE). Enriched composts achieved the highest disease control. P1E was more effective in controlling Clarireedia spp.; pots with infected plants grown on P1E, showed 53.5% less affected area compared to P1t. P2E was more effective against R. solani; results showed 69.3% less affected area compared to P2t and both were effective in S. rolfsii control, with a reduction of 38.5% in P1E and 43.5% in P2E. The larger population of Trichoderma spp. observed in the enriched substrates associated to the greater enzyme activity, namely and N-acetyl-β-glucosaminidase, standing out in P2E, will have contributed strongly to the biocontrol of the studied diseases. An increase in some macro and micronutrients was observed in the enriched heat-treated substrates.